Precision Prediction of Knitted Fabric Loop Length Through Online Monitoring of Yarn Input Tension and Course Length-A Mathematical Approach for Circular Weft Knitting With Positive Storage Feeding - Hossain, A.K.M. Mobarok; Ali, Abu Rayhan Md. (European Scientific Journal, ESJ, 2017)
A model in the form of an equation has been developed based on the mechanical consideration of yarn during dynamic circular weft knitting process that runs with positive storage feed system. The predicted course length through this model has been compared with that found from actual fabric by a recognized apparatus, i.e. HATRA Course Length Tester. The ttest was carried out over the obtained results for statistical analysis purpose. It was observed that for spun polyester knitted fabric, as used in the experimental part, the model worked very effectively through precision prediction by showing very low average mean difference in predicted course length from that measured from the actual fabric. The t-values and corresponding p-values proved the difference between the predicted and actual results statistically significant and thus opened the scope for further investigation and calibration.